Sistem Penunjang Keputusan dalam Pemilihan Program Studi di Perguruan Tinggi Menggunakan Metode Differential Aptitude Test - Jauhari, Tantowi (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
The purpose of making decision support systems in the selection of study programs in Higher Education using differential aptitude test method is to help identify and determine the interests and talents of students. The methodology used in the development of this system is the System Development Life Cycle (SDLC), and the calculation method for measuring interests and talents of students using the method of psychological tests Differential Aptitude Test (DAT). DAT is a test of verbal, numerical and abstract thinking skills. To making this application uses two tools, XAMPP to run applications offline and to create a database, and Sublime Text to create coding. The programming languages used in this application are PHP and HTML programming languages. Based on the tests conducted, it can be concluded that by using this application time calculation results from Differential Aptitude Test will be far faster and can help teachers to perform computerized student data collection.